Attenuation of dissolved metals in neutral mine drainage in the Zambian Copperbelt - Sracek, Ondra; Filip, Jan; Mihaljevič, Martin; Kříbek, Bohdan; Majer, Vladimír; Veselovský, František (Environmental monitoring and assessment, 2011)
Behaviour of metals like Cu and Co was studied in nearly neutral (pH ≥ 6.4) mine drainage seepage in a stream downgradient of a tailing dam at Chambishi site in the Copperbelt of Zambia. They are attenuated by precipitation of ferruginous ochres that incorporate significant quantities of metals. Using chemical analysis, X-ray powder diffraction and Mössbauer spectroscopy, we show that the ochres are composed mostly of amorphous ferric hydroxide. Close to the seepage face, the total Fe content of ochres increases due to precipitation of amorphous ferric hydroxide, but total Fe in sediment decreases further downstream. The stream then flows through wetland (dambo) where the remaining fraction of metals is removed. During rainy periods, increased flow rate may result in re-suspension of ochres, increasing thus the mobility of metals. Major ions like sulphate are conservative at the start of the dry period (May), but gypsum may probably precipitate later at the end of the dry period. Sequential extractions of bulk sediments indicate that Mn behaves differently to Fe, with a trend of increasing Mn with distance from the tailing dam. There is much more Fe than Mn in residual (Aqua Regia) fraction, indicating that amorphous ferric hydroxides are transformed to more crystalline phases deeper in sediment. Environmental impact of mine drainage is relatively limited due to its neutral character.
Keywords: železité sloučeniny; Zambie; Environmental Monitoring; monitorování životního prostředí; Zambia; Ferric Compounds; kovy; hornictví; Metals; difrakce rentgenového záření; X-Ray Diffraction; Mining